Peranan Kredit Usaha Rakyat (KUR) Terhadap Pengembangan UMKM Di Kabupaten Sinjai - Alfira, Alfira; Nurdin, Fadilah; Hikmah, Aulia Nurul; Yudiyanti, Ervina; Gustiana, Gustiana; Fatimah, St; Asmiranda, Asmiranda (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2023)
MSMEs in Sinjai Regency face capital-related challenges hindering their business development and growth. Consequently, government intervention is imperative to address these issues. Kredit Usaha Rakyat (KUR) is a government program aimed at empowering MSMEs. This research aims to investigate the distribution procedures and the role of KUR in fostering MSME development in Sinjai Regency, utilizing a qualitative approach with a focus on fieldwork. The findings reveal a two-stage process for obtaining KUR: initial application and subsequent repayment. Mandiri Bank offers tailored credit limits to match the needs and business types of MSMEs, thereby preventing default risks. Moreover, KUR significantly contributes to enhancing MSME profitability, increasing income levels, and improving overall performance. These outcomes underscore the crucial role of KUR in advancing MSMEs in Sinjai Regency, thereby facilitating economic growth and sustainability at the local level.